Potential use of amino acids analysis for distinguishing bovine and porcine gelatins - Rusli, Norakasha; Mat Hashim, Dzulkifly; Che Man, Yaakob; Mustafa, Shuhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
Reverse Phase High Performance Liquid Chromatography (RP-HPLC) with pre-column derivatisation was used to obtain amino acid profiles of bovine and porcine standard gelatin samples from Sigma and Merck. Partial least-squares (PLS) regression was used to establish a calibration model and the R2 obtained was 0.991 and 0.983 for Sigma and Merck samples,respectively. Classification and characterization of the amino acids were based on principal components analysis (PCA). The results of PCA score plot showed that the method developed is capable of distinguishing gelatin sources by utilizing the main amino acids present in gelatin which are glycine, proline and hydroxyproline, as a potential biomarkers. The RP-HPLC ensures accurate characterization of protein and amino acids. Besides that, it is a fast, repeatable and reliable method to be apply as routine work. It is believe that this method can be used to determine the unknown source of raw gelatins.